Inorganic nutrient regulation of bacterioplankton heterotrophic activity in an estuarine system (Ria de Aveiro, Portugal) - Cunha, A.
This article reports on the study of the regulatory effect of dissolved inorganic nitrogen and phosphorus on the rates of bacterial heterotrophic activity in a mesotrophic estuarine system (Ria de Aveiro, NW Portugal) along a seasonal timeframe. Ectoenzymatic activity, analysed as the rate of hydrolysis of fluorescent substrate analogues, and monomer uptake, estimated from the incorporation of radioactive glucose and leucine, were studied as descriptors of bacterial heterotrophic activity. The availability of dissolved inorganic nitrogen (DIN) was estimated as the sum of the concentrations of nitrate, nitrite and ammonium, and soluble reactive phosphorus (SRP) was determined as an estimate of inorganic phosphorus. The average ratio between DIN and SRP indicates that, generally, N was not a limiting nutrient. Maximum rates of potential aminopeptidase and β-glucosidase activities showed a global positive correlation with DIN. Under low concentrations of DIN, a tighter coupling between aminopeptidase potential activity and leucine incorporation was also observed. In conditions of N-limitation of phytoplankton growth, there was a negative relation between DIN concentration and maximum rates of leucine and glucose incorporation. The results were interpreted as an indication that aminopeptidase potential activity can partially supply organic N sources and that under distinct stoichiometric scenarios, different steps of the pathways of bacterial dissolved organic matter utilisation are affected. Under non-N-limiting situations, DIN stimulates extracellular hydrolysis, whereas under N-limiting conditions, DIN inhibits amino acid uptake.